Inequalities in social capital and health between people with and without disabilities. (February 2015) - Mithen, Johanna; Aitken, Zoe; Ziersch, Anne; Kavanagh, Anne M.
Abstract: The poor mental and physical health of people with disabilities has been well documented and there is evidence to suggest that inequalities in health between people with and without disabilities may be at least partly explained by the socioeconomic disadvantage (e.g. low education, unemployment) experienced by people with disabilities. Although there are fewer studies documenting inequalities in social capital, the evidence suggests that people with disabilities are also disadvantaged in this regard. We drew on Bourdieu's conceptualisation of social capital as the resources that flow to individuals from their membership of social networks. Using data from the General Social Survey 2010 of 15, 028 adults living in private dwellings across non-remote areas of Australia, we measured social capital across three domains: informal networks (contact with family and friends); formal networks (group membership and contacts in influential organisations) and social support (financial, practical and emotional). We compared levels of social capital and self-rated health for people with and without disabilities and for people with different types of impairments (sensory and speech, physical, psychological and intellectual). Further, we assessed whether differences in levels of social capital contributed to inequalities in health between people with and without disabilities. We found that people with disabilities were worse off than people without disabilities in regard to informal and formal networks, social support and self-rated health status, and that inequalities were greatest for people with intellectual and psychological impairments. Differences in social capital did not explain the association between disability and health. These findings underscore the importance of developing social policies which promote the inclusion of people with disabilities, according to the varying needs of people with different impairments types. Given the changing policy environment, ongoing monitoring of the living circumstances of people with disabilities, including disaggregation of data by impairment type, is critical. Highlights: Australian adults with disabilities have less access to social capital. Australian adults with disabilities have poorer self-rated health. Lower levels of social capital explain little of the health inequalities. People with psychological and intellectual impairments fare worst.